Innovation Development Programmes for the State-owned Companies: First Results - Mikhail Gershman (Foresight and STI Governance, 2013)
Enhancing innovation performance in the industrial sector of the Russian economy is a long overdue. Since 2010 the government has conducted a kind of «incumbent» policy approach, encouraging mainly the largest state-owned companies. The latter are obliged to elaborate and implement innovation development programmes (IDPs) in order to accelerate modernization of the Russian economy and increase demand for innovation.